Hermeneutics Of Social Interaction Relations In Islam - Amin, Surahman; Rasid, Ruslan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study examines how social interaction in Islam is then able to give an attitude of tolerance among religious people, especially contained in Q.S Al-Baqarah/2:120 and Q.S Al-Fath/48:29.The methodology used in this study is Hans Georg Gadamer's hermeneutics with Tashihiko's semantic approach. The aim is to